Antimüllerian hormone and adiposity across midlife among women in Project Viva. Issue 3 (4th March 2023) - Francis, Ellen C.; Oken, Emily; Hivert, Marie-France; Rifas-Shiman, Sheryl L.; Chavarro, Jorge E.; Perng, Wei
Abstract : Low antimüllerian hormone (AMH) at baseline was associated with greater adiposity concurrently and across ~ 9 years of follow-up. Whether low AMH is a useful marker of metabolic risk across mid-life requires further research. Abstract: Objective: This study aimed to examine the association of antimüllerian hormone (AMH) with concurrent and prospective measures of adiposity during approximately 9 years of follow-up. Methods: Participants were 697 parous women from the Project Viva prebirth cohort without polycystic ovarian syndrome. We measured AMH at approximately 3 years postpartum (baseline). Outcomes were weight, body mass index (BMI), and waist circumference assessed at baseline, 4, and 9 years later; % body fat was assessed by bioimpedance at the 4- and 9-year visit. We used linear mixed-effect models including all outcome time points and accounting for age across follow-up and hormonal contraception prescription. In an additional model, we further adjusted for height. Results: Median AMH was 1.97 ng/mL (interquartile range, 0.83-4.36 ng/mL), 29.1% had AMH <1.0 ng/mL, and mean age at AMH measurement was 36.7 years (SD, 4.9 y; range, 20-48 y). AMH was inversely associated with average weight, BMI, and waist circumference over follow-up. In age-adjusted models, women with AMH <1.0 versus ≥1.0 ng/mL were 4.92 kg (95% CI, 2.01-7.82 kg) heavier, had a 2.51 cm (95% CI, 0.12-4.89 cm) greater waist circumference, and a 1.46 kg/m 2 (95% CI, 0.44-2.48 kg/m 2 ) greater BMI across the 9 years of follow-up. Findings were similar after covariate adjustment and when AMH was modeled continuously. AMH was also inversely associated with higher fat mass %; however, the CI crossed the null. Conclusion: Low AMH at baseline was associated with greater adiposity concurrently and across approximately 9 years of follow-up. Whether low AMH is a useful marker of metabolic risk across midlife requires further research.